Immunohistochemical evaluation of cardiac connexin43 in rats exposed to low-frequency noise - Antunes, Eduardo (2013)
"Introduction: Low-frequency noise (LFN) leads to an abnormal proliferation of collagen and development of tissue fibrosis. It has been shown that myocardial fibrosis in association with gap junction remodeling occurs in several cardiac diseases and can be implicated in the development of ventricular tachyarrhythmias. We previously reported a strong development of myocardial fibrosis induced by LFN in rats but it is not known whether LFN induces any modification on cardiac connexin43 (Cx43). Objectives: The aim of this study was to evaluate modifications on cardiac Cx43 induced by LFN in Wistar rats. Methods: Two groups of rats were considered: A LFN-exposed group with 10 rats submitted continuously to LFN during 3 months and a control group with 8 rats. The hearts were sectioned from the ventricular apex to the atria and the mid-ventricular fragment was selected. The immunohistochemical evaluation of Cx43 was performed using the polyclonal antibody connexin-43m diluted 1:1000 overnight at 4°C. Quantifications of Cx43 and muscle were performed with the image J software and the ratio Cx43/muscle was analyzed in the left ventricle, interventricular septum and right ventricle. Results: The ratio Cx43/muscle was significantly reduced in LFN-exposed rats (p=0.001). The mean value decreased 46.2%, 22.2% and 55.6% respectively in the left ventricle (p=0.008), interventricular septum (p=0.301) and right ventricle (p=0.004). Conclusions: LFN induces modifications on cardiac Cx43 in rats. The Cx43 reduction observed in our study suggests that LFN may induce an arrhythmogenic substrate and opens a new investigational area concerning the effects of LFN on the heart."